Peran Ganda Single Parent: antara Kepala Rumah Tangga dan Pola Asuh Anak - Fajar Indarsih (Jurnal Pendidikan Islam Anak Usia Dini Al-Amin, 2024)
Family is the relationship between husband and wife or parents with children. Each of them has a role, the father as full responsibility, the mother is the father's partner in managing household affairs. Both are responsible for the basic needs of the family, such as clothing, food, and shelter. Unlike Single Parents, they struggle alone to meet all family needs. This paper attempts to describe the dual role of Single Paren. Method The research method uses qualitative with the type of literature research. While the method of collecting data is documentation. The result of the study was that single parent parents have a dual role. The main role is to meet the basic needs of the family. Such as clothing, food, and shelter. Ideally, the fulfillment of basic needs in the family is carried out jointly between husband and wife. The husband earns a living by working or both working and managing finances. The results of a married couple's money collection can be useful appropriately. In addition to meeting the basic needs of the family, there is also no less important, namely children's basic education. Children's basic education is called tarbiyatul ula, which is education that must be given to children when children are still young. Children's basic education cannot be replaced with anything. Conditions and situations experienced by parents should not leave important things for the child's future life.